Trust Building in the Collaborative Governance Process of Implementing Village Fund Policy: Case Study of Tanah Abang Selatan Village, Penukal Abab Lematang Ilir Regency - Suandi Suandi; Yuliana Yuliana; Susi Lawati; Amir Mahmud (Journal La Sociale, 2024)
Trust building is a component of collaborative governance that involves face-to-face interaction, dedication to the process, mutual understanding, and short-term achievements. This study examines and outlines the various aspects of establishing confidence in the execution of village finance policies, based on the viewpoint of the Collaborative Governance Process theory. The study was carried out at Tanah Abang Selatan Village, which has been allocated village finances since 2015. Empirical evidence demonstrates that the trust actors place in the collaborative governance process can be beneficial in facilitating the achievement of actor support, cooperation, commitment, and successful policy implementation. Nevertheless, the existing literature on collaborative governance indicates a scarcity of studies on establishing trust in policy execution, particularly in the context of implementing village fund regulations. The findings of this study demonstrate that the establishment of trust among participants in the Collaborative Governance process significantly enhances the efficacy of implementing the village fund policy in Tanah Abang Selatan Village, Tanah Abang District, Penukal Abab Lematang Ilir Regency (PALI).